Efecto clínico y metabólico de una intervención multidisciplinaria en el marco de un programa de atención integral para niños y adolescentes con obesidad. - Zuluaga, Nora Alejandra; Osorno, Adriana; Lozano, Alba; Villada, Óscar (Biomédica: Revista del Instituto Nacional de Salud, 2020)
Introduction: The approach to childhood obesity requires multidisciplinary programs including all the dimensions susceptible to management. Objective: To describe the clinical and metabolic changes in patients with obesity after a comprehensive care program for childhood obesity. Materials and methods: We conducted a retrospective observational and analytical study in a cohort of patients between 6 and 17 years old treated in the obesity program at the Hospital Universitario San Vicente Fundación (2012-2015). We carried out multidisciplinary care and educational intervention. Anthropometric and laboratory variables were evaluated both at admission to the program and in the last evaluation and statistical differences were sought according to the follow-up time. Results: We evaluated 53 patients, of whom 52.8% were men, with an average age of 11 ± 2 years. The follow-up extended for 18 ± 6 months though 30% of the patients were followed for 31 to 36 months. There was a decrease in the BMI (Z score) between admission (2.75 ± 0.58 and the last control (2.32 ± 0.63) with a p-value of 0.000 (95% CI: 0.27 -0.58); 79.25% of the patients reduced the BMI Z score. This decrease was significant regardless of the follow-up time. The proportion of patients with a BMI Z score >3 decreased from 33.4% to 14.6%. The number of positive criteria for metabolic syndrome decreased in the follow-up. Triglycerides and HbA1c were the metabolic variables that improved significantly. Conclusions: The management of childhood obesity with an interdisciplinary intervention associated with continuous group educational support can significantly impact on clinical and metabolic changes. It is necessary to continue monitoring over time to prevent relapse.